Pulmonary venous structural remodelling in a canine model of chronic atrial dilation due to mitral regurgitation - Sun, Qi (Pulsus Group Inc, 2008)
OBJECTIVE: Structural remodelling plays an important role in the genesis and maintenance of atrial fibrillation (AF). Although some studies that associate structural remodelling with atrial dilation have been reported, structural pulmonary venous (PV) remodelling due to chronic atrial dilation remains unclear. METHODS: Six sham dogs and five mitral regurgitation (MR) dogs (three months after partial mitral valve avulsion) were studied. Separate cryosections from the PV and left atrium (LA) were immunolabelled with antibodies against connexin (Cx) 40 and Cx43 and analyzed by confocal laser scanning microscopy. Tissue samples from the PV and LA were stained with hematoxylin and eosin, and Masson’s trichrome. RESULTS: In MR models, a decrease in Cx40 (0.57±0.2% versus 1.18±0.3%, P<0.05) and Cx43 (0.48±0.2% versus 1.56±0.5%, P<0.05) expression was observed compared with sham dogs. The distribution pattern of Cx40 and Cx43 changed from homogeneous to heterogeneous. Gap junction remodelling was not observed in the LA. In Masson’s trichrome-stained sections from MR dogs, regions with increased interstitial fibrosis were present in the PV. Thickness in the PV and the PV-LA junction did not change in the MR group. CONCLUSION: The present study demonstrated a decrease in Cx40 and Cx43 expression and increased interstitial fibrosis in PV due to MR. These changes may potentially be a mechanism that renders the dilated atria more susceptible to AF.